Design of a Harvesting Machine for the Collection of Fresh Asparagus using Artificial Vision - Requena-Rodríguez, José; Rodríguez-Silva, Ronaldo; Zarate-Perez, Eliseo (LACCEI, 2024)
Green asparagus is one of the most important agricultural products in the agricultural sector of Peru, positioning the country as the world's second-largest producer of these vegetables. However, the lack of prototypes and innovative technologies to address the needs of the agro-industry has adversely affected asparagus exports. Furthermore, the artisanal work modality and climatic conditions adversely impact the harvesting and quality of asparagus. To mitigate product quality issues, the implementation of an artificial vision-based recognition system is proposed. The objective of this study is to design a harvesting machine for the collection of green asparagus using this technology. The results present the detailed design of the machine, including all its systems and mechanisms. Additionally, it is estimated that the machine would take 7.5 seconds to harvest one asparagus. In the artificial vision tests, a recognition accuracy of 95% was achieved for the categories of asparagus.